(untitled) (University of Khartoum Journal of Agricultural Sciences, 2022)
In faba bean, the genotypically heterogeneous structure of its population has an important impact on yield performance and remains the major constraint a plant breeder has to contend with to improve the crop yield. The aim of this study was to evaluate the effect of heterogeneity and heterozygosity on yield performance of the semi-arid grown faba bean. Five faba bean inbred lines (in S6 generation), F1 and F2 generations as well as mixtures formed by blending an equal amount of seeds from each of them to produce line mixture, F-1 mixture and F2-mixtures were used to execute the experiment. The seeds of the pure lines, lines mixture and F1-and F2-mixture were grown in two consecutive seasons (2014/2015-2015/2016) at the Experimental Farm, Faculty of Agriculture, Shambat in a randomized complete block design with three replicates. Data were collected on yield and yield components. Heterogeneity in lines mixture caused a positive and significant increase of +16% in number of pods per plant and 11% increase in both 100-seed weight and yield compared to pure lines performance, whereas heterogeneity in "pure lines+ F1-hybrid and that in pure lines mixture+ F1- hybrid mixture gave significant positive yield of 28% and 24% , respectively when compared to the performance of F2 and F2 mixture. Heterozygosity in F1 gave significant positive yield increase of 67% when compared to lines performance, whereas heterozyosity in F1-mixture gave significant yield increase of 60% when compared to lines mixture. The same effect was shown by yield components. The results clearly indicate the great positive effect of heterozyosity compared to that of heterogeneity, which indicate the possibility of production of synthetic cultivars as alternative to the still not yet commercially produced hybrids in faba bean.